Analysis of business feasibility and trade system for rattan crafts in Rumbai district, Pekanbaru City - Latifah, Siti; Agus Purwoko; Sindy Hutapea (Global Forest Journal, 2023)
Rattan is one of the commodity timber forest products used as raw material for the rattan industry. One of the small businesses that is quite developed in Rumbai District, Pekanbaru City is the rattan handicraft business which is a traditional small industry and is a family business. This study aims to determine the business feasibility and trading system of the rattan handicraft trade. This research was conducted with a quantitative and qualitative descriptive approach. The method used for data collection is a field survey through observations, interviews, and questionnaires on rattan craftsmen and Trade Units (UD). UD Rattan Crafts in Rumbai can be said to be worthy of continuing. This is because the NPV value of the trading business in Rumbai is > 0, IRR > from interest rates, and BCR > 1. Analysis of the trading system shows that there are trading system functions that are used, namely the exchange function, physical function, and facility function.